Lactiplantibacillus plantarum LAB12 induced neuroprotection through the gut-brain axis / Muhammad Syukri Noor Azman … [et al.] - Noor Azman, Muhammad Syukri; Siong, Meng Lim; Fei, Tieng Lim; Ramasamy, Kalavathy (Faculty of Applied Sciences, 2023)
It is increasingly recognized that probiotic lactic acid bacteria (LAB) could potentially reverse dysbiosis and suppress neuroinflammation via the Gut-Brain Axis. The present study investigated Lactiplantibacillus plantarum LAB12-mediated crosstalk between the Enteric Nervous System (ENS) and the Central Nervous System (CNS) by assessing the beneficial effects on memory, modulation of major neurotransmitters, neuropeptides, and gut hormones as well as mitochondrial functions in vivo. To this end, Sprague Dawley rats (male, three months old) were administered with an antibiotic cocktail (i.e., imipenem, vancomycin, ampicillin, ciprofloxacin, and metronidazole) before being challenged with 0.25mg/kg LPS to mimic germ- free gut and neuroinflammation. The rats were divided into groups (n=8/group) of wild-type, lipopolysaccharide (LPS) control, LAB12+LPS, antibiotics+LPS (ABX), and ABX+LAB12 (ABXL). The rodents were then subjected to the Morris Water Maze (MWM) Test. Rat hippocampi and colons were harvested and subjected to biochemical analyses and metabolism assays. It was found that ABXL spent relatively more time in the platform zone (+16%) as opposed to their ABX counterparts. In terms of mitochondrial enzymes, the ABXL group was presented with increased Complex III enzyme activities in their cortices (+57 %; p<0.05) and hippocampi (+33 %; p<0.01) when compared to the ABX group. In terms of neurotransmitters, the ABXL group significantly increased the 5-hydroxytryptamine (5-HT) level (+32%, p<0.05) in the hippocampi when compared to the ABX group. The ABXL group also significantly increased ghrelin (GHRL) level (+85%, p<0.05), a gut hormone, in the hippocampi, when compared to ABXL. Nevertheless, ABXL did not bring about significant changes against neuropeptides [neurotensin (NT), neuropeptide Y (NPY), and vasoactive intestinal peptide (VIP)] in both the hippocampi and colons. The present findings implied that LAB12 could potentially improve memory impairment via the modulation of signaling pathways between the ENS and the CNS.